What works in schools : translating research into action - Marzano, Robert J. (Gale virtual reference, 2003)
Provides information for schools and teachers on how to improve student achievement. Discusses which instructional strategies really work; why data is a critical component to school improvement; how important collegiality and professional development are; and what types of parental and community involvement make a difference.